School-to-work transition challenge: a social profile of young workers in Malaysia - Rokis, Rohaiza (2012)
School-to-work transition is indeed a confusing and difficult period for young people. Youth employability is often hindered by the fact that young people lack the right work attitude required by the employment market. In Malaysia, the age youth is defined as those between 15 and 40 years old (Lee, 2006). However, the particular concern of this research deal with youth at the age of 15 to 24 years old. This stage of life is crucial in determining young peoples’ paths to achieving productive employment and decent work. While rapid globalisation and technological change may offer new opportunities for productive work and incomes, still youths have been facing the problem of unemployment.